France, the European Economic Community and sub-Saharan Africa, the Agreement of Yaounde (in July, 1963) in the Agreement of Lomé 1 (in February, 1975) - (:unkn) unknown (My University, 2014)
France has obtained from its partners the inclusion of the overseas territories in the Treaty of Rome which established the EEC. The goal was to maintain relations between the mainlands and the former colonies in a new context during the decolonisation.Between 1958 and 1963, the Six experienced a partnership system with third countries, particularly the African and Malgach Associated States (AMAS) which allowed to maintain particular economic ties with these sovereign states on behalf of development aid. The July 1963 Convention of Yaounde marked the will of the Six to institutionalise and coordinate their relations with African and Malgache third countries and laying the foundations of cooperation policy, consolidated by the renewal of this convention. On the commercial level, These agreements were based on mutual preferencial tariffs and quotas and financial and technical assistance.At the end of a decade of association, the development aid assessement was very poor, except for the field of education and training where an increase in schooling was witnessed in most of the AMAS, but in terms of economy, results were insignificant: the preferences they benefited from gradually decreased into little, They still remained very dependent and heavily indebted. Their economy was still based on the export of tropical products and mining and the very unbalanced terms of trade.
Keywords: African Research